2010
DOI: 10.1002/bjs.7026
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of preoperative oral carbohydrate treatment in major abdominal surgery

Abstract: ACTRN012605000456651 (http://www.anzctr.org.au).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
2
19

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 29 publications
7
113
2
19
Order By: Relevance
“…This result appropriate with the research by Mathur et al at New Zealand, on patient undergoing elective major abdominal surgery, that compared sample groups who got oral glucose solution preoperatively on night and morning 2 hours before induction of anesthesia compared with placebo groups that result significant decrease in cortisol level on the sample groups who got oral glucose solution than placebo groups on the first day after surgery [7]. This result also matched to the theoretical concept that administration of oral glucose solution preoperatively can trigger the insulin secretion, thus change the patient's metabolic status from fasted state to fed state [8].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This result appropriate with the research by Mathur et al at New Zealand, on patient undergoing elective major abdominal surgery, that compared sample groups who got oral glucose solution preoperatively on night and morning 2 hours before induction of anesthesia compared with placebo groups that result significant decrease in cortisol level on the sample groups who got oral glucose solution than placebo groups on the first day after surgery [7]. This result also matched to the theoretical concept that administration of oral glucose solution preoperatively can trigger the insulin secretion, thus change the patient's metabolic status from fasted state to fed state [8].…”
Section: Discussionsupporting
confidence: 75%
“…The level of significance was p<0.05. The entire data analysis of this study will be done with SPSS version 20 for Windows [7].…”
Section: Methodsmentioning
confidence: 99%
“…27,[154][155][156] In contrast, the results of a larger randomized controlled trial showed no significant benefit. 157 A recent meta-analysis, however, suggests that preoperative administration of oral carbohydrates accelerates recovery after major abdominal surgery. 158 The current ERAS guidelines, therefore, recommend the routine use of preoperative carbohydrate drinks.…”
Section: Assessment Of Catabolism Before Surgerymentioning
confidence: 99%
“…24 Ben zer olum suz so nu ca sa hip Mat hur ve ark.nın ça lış ma sın da da kon trol gru bu kul la nıl -ma mış, "ra hat sız lık his si" gi bi sub jek tif bir his değer len di ril miş ve la pa ros ko pik ve ya açık cer ra hi ler, epi du ral anes te zi uy gu la nan ve ya uy gu lan ma yan has ta lar bi r a ra da de ğer len di ril miş tir. 25 Bu lan tı ve kus ma pos to pe ra tif dö nem de has talar açı sın dan ağ rı dan bi le da ha ra hat sız edi ci ola bilen, ta bur cu luk sü re si ni uza ta rak mor bi di te ve ma li ye ti ar tı ran bir yan et ki dir. Ha u sel ve ark.…”
Section: Tar Tiş Maunclassified